Pengaruh Pengalaman Konsumen dan Citra Merek Lokal terhadap Minat Berkunjung Ulang dengan Kepuasan Konsumen sebagai Variabel Mediasi (Studi pada pelanggan warung kopi dengan brand lokal di Kota Pontianak) - B1021161036, HENNI OKTAVIANI (Jurnal Manajemen Update, 2020)
This reseach is conducted to find out the effect of consumer experience variables, local brand image, and customer satisfaction on revisit intention to a coffee shop with a local brand in Pontianak. This research is included in descriptive research with survey method. The type of research used in this research is causal associative research, and data collection techniques are through distributing questionnaires through the google from application. The population in this study were all consumers who had visited coffee shops with local brands in Pontianak City such as Aming Coffe, Asiang Kopi, and Bang Edi Coffee. The number of samples in this study was 100 respondents. Sampling was conducted using non-probability sampling techniques with purposive sampling method and analysis tools, namely path analysis (path analysis).The results showed that the variables of consumer experience, local brand image, and customer satisfaction significantly influence the interest in a repeat visit. The ability of these three variables in explaining their influence on the behavior of revisiting interest was 55.9% while the remaining 44.1% was explained by other factors outside the research model. Keywords: Consumer experience, local brand image, customer satisfaction, revisit intention.DAFTAR PUSTAKA Amilia, S. (2017). Pengaruh Citra Merek, Harga, dan Kualitas Produk terhadap Keputusan Pembelian Handphone Merek Xiaomi di Kota Langsa. Jurnal Manajemen Dan Keuangan, Vol.6, No.1, Mei 2017.Azhari Iqbal, M., Fanani, D., & Mawardi Kholid, M. (2015). Pengaruh Customer                   Experience Terhadap Kepuasan Pelanggan Dan Loyalitas Pelanggan (Survei Pada Pelanggan Kfc Kawi Malang). Jurnal Administrasi Bisnis (JAB)|Vol. 28 No. 1 November 2015. Behboudi, I. & Hosseini, S. H. K. (2017). Brand trust and image: Effects on customer satisfaction. International Journal of Health Care Quality Assurance. Retrieved from https://doi.org/10.1108/IJHCQA-04-2016-0054.Bigne, J. E., Sanchez, M. I., & Sanchez, J. (2001). Tourism image, evaluation variables and after purchase behaviour: Inter-relationship. Tourism Management, 22, 607-616.Chotimah, S., & Wahyudi, D. H. (2019). Pengaruh Perceived Value Terhadap Revisit      Intention: Mediasi Customer Satisfaction Pada Pengunjung Jawa Timur Park I Batu. EKOBIS – Ekonomi Bisnis Vol. 24 No. 1 | Mei 2019 | Halaman 1-11.Dewi, I.A.I., & Laksmidewi, D. (2015). Pengaruh Customer Experiences Terhadap Revisit Intention Dengan Mediasi Learning In Museum Dan Visitor Satisfaction Di Museum Wayang. Jurnal Manajemen [Vol. 12 No. 2 November 2015.Gentile, C., Spiller, N., & Noci, G. 2007. How to sustain the customer experience: An overview of experience components that co-create value with the customer. European management journal, 25(5), 395-410. https://doi.org/10.1016/j.emj.2007.08.005 Ghozali, I. (2011). Aplikasi Analisis Multivariate dengan Program IBM SPSS 19. Semarang: Badan penerbit Universitas Diponegoro.Hadiyono, N., & Yonathan Palumian, Y. (2019). Pengaruh Fasilitas Dan Citra Merek Terhadap Niat Pembelian Ulang Produk Starbucks Di Surabaya. Agora Vol. 7, No. 2, (2019).Han Heesup, et al. (2019). Impact of core-product and service-encounter quality, attitude, image, trust and love on repurchase: Full-service vs low-cost carriers in South Korea. International Journal of Contemporary Hospitality Management, https://doi.org/10.1108/IJCHM-05-2018-0376Harsiska, N. (2019). Pengaruh Word Of Mouth Dan Aksesibilitas Terhadap Destination Image Dan Dampaknya Pada Minat Berkunjung Ulang (Studi Pada Objek Wisata Kota Singkawang). Universitas Tanjungpura, Indonesia.Hosseini, S.H.K., & Behboudi, L. (2017). Brand trust and image: effects on customer satisfaction. International Journal of Health Care Quality Assurance, Vol. 30 Issue: 7, pp.580-590, https://doi.org/10.1108/IJHCQA-04-2016-0054.Isnaini, P.R., & Abdillah, Y. (2018). Pengaruh Citra Merek Destinasi Terhadap Keputusan Berkunjung Dan Kepuasan Pengunjung Serta Dampaknya Pada Minat Kunjung Ulang (Survei Pada Pengunjung Taman Rekreasi Selecta Kota Batu Yang Termasuk Dalam Kategori Generasi Millennial). Jurnal Administrasi Bisnis (JAB)|Vol. 55 No. 2 Februari 2018.Japarianto, E., (2019). Pengaruh Retail Service Quality Terhadap Minat Berkunjung Ulang Mall Di Surabaya Melalui Perceived Quality Dan Customer Satisfaction Sebagai Variabel Intervening. Jurnal Manajemen Pemasaran, Vol. 13, No. 1, April 2019, 17─26.Keller, K.L. (1993). Conceptualizing, Measuring, and Managing Customer-Based Brand Equity Author. Journal of Marketing, Vol. 57, No. 1 (Jan., 1993)Kotler, Philip & Keller, K.L. (2007). Manajemen Pemasaran, Edisi 12, Jilid 1. Jakarta: PT.IndeksKotler, P., & Keller K.L. (2008). Manajemen Pemasaran-Edisi 12: Jilid 1. Indonesia: PT IndeksKotler, P., & Keller K.L. (2009). Manajemen Pemasaran-Edisi 13: Jilid 1. Indonesia: Penerbit ErlanggaKotler, Philip and Keller K.L. (2012). Marketing Management. 14st edition. Prentice Hall: New Jersey.Kuncoro, M. (2013). Metode Riset Untuk Bisnis & Ekonomi: Bagaimana Meneliti dan Menulis Tesis. Indonesia: PT. Gelora Angkasa PratamaMeyer, C., & Schwager, A. (2007). Understanding customer experience. Harvard Business Review, 2, 117-126. https://hbr.org/2007/02/understanding-customer-experience Nasermoadeli, Amir., Choon-Ling, Kwek., Maghnati, Farshad. 2012. Evaluating the Impacts of Customer Experience on Purchase Intention. International   Journal of Business and Management vol.8, No.6 2013.Nuraeni, Bellinda Sofia. (2014). Analisis Faktor-Faktor Yang Mempengaruhi Minat Kunjung Ulang Wisatawan Museum Ranggawarsita Semarang. Jurnal Bisnis STRATEGI Vol. 23 No. 1 Juli 2014.Ongkowidjojo, M. (2018). Pengaruh Citra Merek Dan Kualitas Yang Dipersepsi Konsumen Terhadap Kepuasan Pelanggan Grabcar Di Surabaya. AGORA Vol. 6, No. 2, (2018).Petrik, J.F., Morais, D.D., & Norman,W.C. (2001). An Examination Of The Determinants Of Entertainment Vacation’ Intentions To Revisit, Journal Of Travel Research, 40 (1), 41-48.Pramudita, Y.A., & Japarianto, E. (2013). Analisa Pengaruh Customer Value dan Customer Experience terhadap Customer Satisfaction di De Kasteel Resto Surabaya. Jurnal Manajemen Pemasaran Petra Vol. 1, No. 1, (2013).Pranoto, G. R., & Subagio, H. (2010). Analisa Pengaruh Customer Experience Terhadap Customer Satisfaction Pada Konsumen Di Rosetta’s Cafe & Resto Surabaya. Jurnal Manajemen Pemasaran Petra. Prastyaningsih, Suyadi & Yulianto, E. (2014). Pengaruh Customer Experience Terhadap Repurchase Intention (Survei pada Konsumen KFC Di Lingkungan Warga RW 3 Desa Kandangrejo, Kedungpring, Lamongan). Jurnal Administrasi Bisnis (JAB)|Vol. 16 No. 1 November 2014Prayitno, Y. & Sutanto, E.M. (2018). Analisis Pengaruh Kualitas Produk, Kualitas Layanan, Dan Citra Merek Terhadap Kepuasan Konsumen Bakmi Raja Nikmat Cabang Royal Plaza Surabaya. AGORA Vol. 6, No. 2, (2018).Priansa, D.J. (2017). Perilaku Konsumen: Dalam Persaingan Bisnis Kontemporer. Bandung: AlfabertaRositasari, et al. (2019). Komunikasi Pemasaran Tomcir (Atom Kocir) Dalam Membangun Eksistensi Sebagai Brand Lokal Cirebon (Studi Deskriptif Kualitatif Komunikasi Pemasaran Pada Tomcir (Atom Kocir) Di Kota Cirebon). JURNAL SIGNAL Volume 7 No. 1, Januari - Juni 2019 | Ilmu Komunikasi – FISIP.Saputri, N.A.H. (2019). Pengaruh Customer Experience Terhadap Electronic Word Of Mouth Dengan Customer Satisfaction Sebagai Variabel Mediasi (Studi pada Konsumen Chingu Cafe Yogyakarta). Universitas Negeri Yogyakarta, Indonesia.Scmitt, Be. H. (1999): Experiential Marketing, Journal of Marketing Management, 15:1-3, 53-67. http://dx.doi.org/10.1362/026725799784870496Sekaran, U. (2006). Metode Penelitian Bisnis. Jakarta: Salemba Empat.Senjaya, et al. (2013). Pengaruh Customer Experience Quality Terhadap Customer Satisfaction & Customer Loyalty Di Kafe Excelso Tunjungan Plaza Surabaya: Perspektif B2c. Jurnal Manajemen Pemasaran Petra Vol. 1, No. 1, (2013).Simarmata, B. (2016). Pengaruh citra merek dan daya tarik iklan terhadap keputusan pembelian konsumen produk smartphone Samsung pada mahasiswa Stie Itmi Medan. Jurnal Ilmiah Integritas, 2(1), 1-18. http://www.Jurnalmudiraindure.com/wp-content/uploads/2016/08/PENGARUH-CITRA-MEREK-DAN-DAYA-TARIK-IKLAN-TERHADAP. Siregar, S. (2017). Statistik Parametrik untuk Penelitian Kuantitatif: Dilengkapi dengan Perhitungan Manual dan Aplikasi SPPS Versi 17. Jakarta: Bumi AksaraSmilansky, Shaz. 2009. Experiential Marketing : A Practical Guide To Interactive Brand Experiences. London and Philadelphia: Kogan PageSugiyono (2012). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Indonesia: AlfabetaSolimun, (2011). Analisis Variabel Moderasi dan Mediasi. Program Studi Statistika FMIPA universitas Brawijaya. Malang.Sugiyono (2017). Metode Penelitian Bisnis: Pendekatan Kuantitatif, Kualitatif, Kombinasi, dan R&D. Edisi 3, Bandung: AlfabetaSunyoto, D. (2014). Dasar-Dasar Manajemen Pemasaran – Konsep, Strategi, dan Kasus. Yogyakarta: CAPS (Center of Academic Publishing Service)Tjiptono, F. (2014). Pemasaran Jasa – Prinsip, Penerapan, dan Penelitian. Yogyakarta: C.V ANDI OFFSETTjiptono, F. (2016). Pemasaran Esensi & Aplikasi. Yogyakarta: C.V ANDI OFFSETVentura, Y. C. (2018). Pengaruh Pengalaman Pengunjung, Citra Destinasi Dan Sosial Media Melalui Kepuasan Pengunjung Terhadap Minat Berkunjung Kembali Pada Wisata Telaga Sarangan Di Kabupaten Magetan. Universitas Jember, Indonesia.Wulandari, K. (2015). Analisis Persepsi Pelanggan Atas Dimensi Kualitas Jasa Terhadap Kepuasan Pelanggan Dan Niat Beli Ulang. Jurnal Administrasi Bisnis (2015), Vol.11, No.1: hal. 84–100, (ISSN:0216–1249).Yuniawati, Y., & Finardi, A.D.I. (2015). Pengaruh Customer Experience Terhadap Revisit Intention Di Taman Wisata Alam Gunung Tangkuban Perahu. Tourism And Hospitality Essentials (The) Journal, Vol.Vi.Website:https://amingcoffee.com/https://kumparan.com/hipontianak/3-rekomendasi-coffee-shop-di-pontianak-yang-gunakan-kopi-lokal-1rR0KCyB3WShttps://tanilink.com/bacaberita/138/kopi-dengan-pengolahan-basah-dapat-mendukung-tumbuhnya-bisnis-kopi-dalam-negeri/https://kumparan.com/hipontianak/7-fakta-warung-kopi-asiang-di-pontianak-yang-legendaris-1rHoQiJTDSyhttps://kumparan.com/hipontianak/wali-kota-pontianak-kenalkan-kopi-robusta-lewat-kopi-bang-edi-1rFWGfOeOtehttp://quantpsy.org/sobel/sobel.htm